Poezja Gregora Strnišy w przekładzie Katariny Šalamun-Biedrzyckiej / The Gregor Strniša’s poetry translated by Katarina Šalamun-Biedrzycka - Gawlak, Monika (Przekłady Literatur Słowiańskich, 2009)
The poetry of Gregor Strniša — one of the greatest Slovenian poet of the XX century — is widely presented in Poland by Katarina Šalamun-Biedrzycka. Apart from poetry anthology Silver and moss she also published independent selection of his poetry Odysseus. Presented article considers the translator’s choices on three levels — chosen poetry volumes, poems and translator’s transformations itself. On the level of chosen poetry volumes the translator omits the last three ones, clearly realizing specific for the artist idea of the „cosmic consciousness”. The circle of receiving audience is being devoided of even selective experience of the volumes’ character, in which Strnisa realizes (on the lyrical range) his conception of the world and universe. On the level of poetics translator presents Strniša’s poems only as „degrees of releasing terror” and at the same time limits the perspective of the created reality only to the dimension inspired by existentialist philosophy. Comparing the original text with the translation has proven that they differ significantly. However, Šalamun-Biedrzycka’s translations undoubtedly deserve merit for their pioneering quality.